A relação de hospitalidade entre stakeholders, mobilidade corporativa e meios de pagamento: um estudo de casos múltiplos - JBS, Kontik Franstur e Banco do Brasil - MELLO, Cláudia Cristina Martins de (2016)
This work belongs to Hospitality, Services and Organizations line of research; into this scenario, the author identified the need to investigate how hospitality, corporate mobility and means of payment are related. The research problem was: the influence of hospitality in decisions on the choice of payment methods and their contribution to the competitiveness of an organization?This research had the main objective to understand how hospitality relationship in the practice of corporate mobility and as specific objectives know the practices in corporative mobility related to means of payment, identify the existence of hospitality process in a decision making about means of payment, and understand how the hospitality process impacts on competitiveness in organizations when it is related to the choice of means of payment.To achieve these objectives, an empirical and exploratory research was conducted, whose methodological procedures complied with the following steps. The first step was the lifting of the theoretical framework made based on literature related to the research area. The research used fundamentals of authors such as Gotman (2001, 2009); Lashley and Morrison (2004); Ferreira and Wada (2011); Freeman (1984); Freeman et al. (2010); Zeithaml and Gremler (2010); Hamel and Prahalad (2005) and others. Then, there was a study of multiple cases from advocated by Yin (2005). To perform the series of interviews, we used the method of categorization of Bardin (2011) as well as the analysis of the generated content. Propositions treated in this study were (P1) a relationship based on hospitality influence on the decision to choose the means of payment organizations; (P2) the existing means of payment on the market today meet the needs of organizations and (P3) hospitality is a competitive advantage in the choice of means of payment. The results confirmed partially the first and third proposals and confirmed the second. The organizations selected for this study are such financial institution, private and TMC (Travel Management Company) respectively constituting Bank of Brazil, JBS Brazil and KontikFranstur